Mind and Machine. The New Spaces of Robots and Digitization - Janz, Bruce; Schmiljun, André (ETHICS IN PROGRESS, 2019)
Machines have always been a tool or technical instrument for human beings to facilitate and to accelerate processes through mechanical power. The same applies to robots nowadays – the next step in the evolution of machines. Over the course of the last few years, robot usage in society has expanded enormously, and they now carry out a remarkable number of tasks for us. It seems we are on the eve of a historic revolution that will change everything we know right now. But not only robots have an impact on our life. It is digitization in its entirety, including smart applications and games, that confronts us with new spaces. This special volume of Ethics in Progress tries to broaden our understanding of a philosophical field – robots and digitization – that is still in its infancy in terms of it research and literature.